Energy and economic welfare (cost-benefit analysis of micro-hydro systems in Nepal) - Sanjay Prasad Gorkhali (Ruhr-Universität Bochum, Institut für Entwicklungsforschung und Entwicklungspolitik (IEE), 2005)
Economic welfare of people in the rural areas can be enhanced through increase in agricultural productivity and development of rural enterprises. Both of these approaches depend highly on the accessibility of commercial sources of energy. As there is a high potential for the utilization of hydropower in Nepal and considering that the rural communities are isolated and scattered, micro hydro (MH) systems serve as a viable alternative for enhancing the economic welfare in rural areas. As the establishment of MH systems require considerable resources, it is necessary to first evaluate the systems' economic desirability to gather its net welfare effect on the rural population. Interestingly, the analysis shows that MH systems can be a highly effective means of increasing the economic welfare of people in the rural areas, even though it may be in a weak financial situation. However, bearing in mind the need to ensure the long-term sustainability of these MH systems in delivering services, the financial viability of a system therefore becomes a crucial consideration.
Keywords: 330; Wasserkraft; Energieversorgung; Kosten-Nutzen-Analyse; Nepal